A Study on Medical Malpractices of Doctors and Medical Specialist - B, Tungalagbaigal.; M, Tserenbat.; E, Bayarmaa.; B, Amarbayasgalan.; N, Jolbarys. (Caucasus Journal of Health Sciences and Public Health, 2020)
Any significant study regarding medical malpractices and negligence hasn’t been done in recent years in our country. Therefore, there is a necessity to study the cases which have been considered as medical malpractice and negligence by legislative agencies to identify the root cause of the negligence of liability and suggest a solution to ensuring the right of patients to protect their wellbeing and improving the medical assistance and service capabilities and sufficiency. Medical law is a legal concept that consists of constitutional, administrative, civil, criminal, and labor laws aimed at regulating social relations related to hospitals. Medical malpractices are a record that registers the cases of medical breaches and negligence. Medical malpractices and negligence are defined as follows, qualified and licensed physicians and medical professionals failed to exercise treatment, nursing, prescription of medication, obstetrics, and rehabilitation during treatment in certain level intentionally, carelessly, and failed to fulfill his or her duties under decreed code of conduct and which resulted in injury and even loss to patient health. Ever since the concept of “Medical care law” was mentioned for the first time in Mongolia on “ Glossary of Legal Terms” in 2018, the medical malpractices have been raised. The research examined the current situation and root causes of medical liability breaches in the health sector in connection with the implementation of the revised version of the Criminal Code of Mongolia, and as a foundation study, it has been considered as an innovative by aiming at further improving the legal education of medical professionals.